Las artes plásticas para el desarrollo de la inteligencia espacial en los niños y niñas de preparatoria de la escuela Luis Alfredo Samaniego Arteaga, del cantón Catamayo en el periodo académico 2018-2019 - Yunga Chamba, Deisy Michelle (2020)
This thesis entitled: THE PLASTIC ARTS FOR THE DEVELOPMENT OF SPACE INTELLIGENCE IN THE PREPARATORY CHILDREN OF THE LUIS ALFREDO SAMANIEGO ARTEAGA SCHOOL, OF THE CATAMAYO CANTON IN THE ACADEMIC PERIOD 2018-2019, the general objective was to determine the influence of the plastic arts for the development of spatial intelligence in high school boys and girls; The following methods were used: the scientific, analytical-synthetic, statistical-descriptive; The sample was chosen under the criterion of non-probabilistic consecutive sampling, among the techniques and instruments were present: the survey aimed at teachers and parents, the multiple intelligence test of Gardner CAST (Toy Test) and the observation instrument and evaluation of the spatial intelligence of Beatriz Brunal Vergara applied to 24 students, which allowed diagnosing the problem, identifying that: 96% of children do not master spatial intelligence, by identifying the behavioral and learning traits and referents of spatial intelligence , 41% are low presence and 39% are absent, that is, 80% have difficulties in spatial intelligence; the alternative proposal “With my creative hands, I learn” was applied where the activities applied were evaluated, demonstrating the effectiveness of 75% where the children managed to acquire the skills; when applying the post test, significant changes were reflected, that is, 80% dominated spatial intelligence, where 73% presented notable features in spatial capabilities. It is concluded that the use of plastic arts allows the acquisition of spatial skills and abilities, which contribute favorably to the development of spatial intelligence; they should not be considered as an additional luxury, but a fundamental component of education. High school teachers are recommended to include in the curricular planning the workshop as a pedagogical tool whose activities promote the acquisition of skills and abilities for the development of spatial intelligence in children.